2018
DOI: 10.1088/1361-665x/aaf1e3
|View full text |Cite
|
Sign up to set email alerts
|

A new way to obtain black electrochromism: appropriately covering whole visible regions by absorption spectra of copolymers composed of EDOT and carbazole derivatives

Abstract: There is a limited number of studies in the literature on materials showing electrochromic properties between black and transparent. In this study, black-to-transmissive electrochromic materials have been obtained as a result of electrochemical co-polymerization of carbazole derivatives (Cz1 and Cz2) and EDOT. Homopolymers and copolymers synthesizing different monomer feed ratios have been characterized by electrochemical and spectroelectrochemical methods. A new, simple, and fast method of obtaining black ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The redox switching a * b * traces for each of the polymers (Figure b) show that ECP–Random25, ECP–Random30, and ECP–Random40 all have a * b * values that lie within the color-neutral range (which we define as a * and b * values not deviating from the origin, i.e., within ±10), while ECP–Random20 has its neutral state a * values lying slight above 10, moving into the region of red hue. Results on previously published neutral hue ECPs have been shown to possess color neutrality in their extreme potentials; however, their a * b * values often lie outside of ±10 at intermediate voltages. ,,, As the vibronic features are bleached at different rates, this results in an increase in a * and/or b * values to above 10 before returning to color neutral as the polymer continues to be oxidized. Similarly in a previous ECP blending study where multiple ECPs are mixed to achieve color neutrality, we also see colored intermediate states resulting from the differences in oxidation potential of the various polymers .…”
Section: Resultsmentioning
confidence: 99%
“…The redox switching a * b * traces for each of the polymers (Figure b) show that ECP–Random25, ECP–Random30, and ECP–Random40 all have a * b * values that lie within the color-neutral range (which we define as a * and b * values not deviating from the origin, i.e., within ±10), while ECP–Random20 has its neutral state a * values lying slight above 10, moving into the region of red hue. Results on previously published neutral hue ECPs have been shown to possess color neutrality in their extreme potentials; however, their a * b * values often lie outside of ±10 at intermediate voltages. ,,, As the vibronic features are bleached at different rates, this results in an increase in a * and/or b * values to above 10 before returning to color neutral as the polymer continues to be oxidized. Similarly in a previous ECP blending study where multiple ECPs are mixed to achieve color neutrality, we also see colored intermediate states resulting from the differences in oxidation potential of the various polymers .…”
Section: Resultsmentioning
confidence: 99%
“…An interesting recent work focuses on electrochemical copolymerisation of EDOT with either of two conjugation restrained, star-shaped triazine-core, carbazole-arm derivatives [ 42 ]. Tuning the monomer feed ratio to optimise colouration efficiency, and tailoring the thickness of electrochromic layers, through careful electropolymerisation conduct, to maximise contrast ratios, afforded multielectrochromic layers, switching from clear to black through at least three intermediate hues.…”
Section: Pursuing the Goalmentioning
confidence: 99%
“…The same authors recently reported the electrochemical polymerization of an original carbazole-thiophene unit substituted with an alkyl chain in position 3, which sterically inhibited one of the processes that occur due to a high potential and resulted in the formation of a material with a more regular structure [47]. In another study, electrochemical copolymerization of carbazole derivatives and ethylenedioxythiophene (EDOT) led to the formation of original materials with electrochromic properties between black and transparent [48]. Similarly, Aydin et al electropolymerized copolymers of carbazoles with thiophene, EDOT and pyrrole [49].…”
Section: Introductionmentioning
confidence: 99%